2021
DOI: 10.3390/f12111504
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Alnus glutinosa L. and A. incana (L.) Moench. Hybrids in Natural Forests Using Nuclear DNA Microsatellite and Morphometric Markers

Abstract: Two alder species (Alnus glutinosa and A. incana) have overlapping distribution, naturally occur in Lithuania, and are considered ecologically and economically important forest tree species. The objective of our study was to estimate the likelihood of spontaneous hybridizations between native alders in natural stands of Lithuania based on leaf morphology and nuclear microsatellite markers. The sampled trees were assigned to the three taxonomic groups of A. glutinosa, A. incana, and potential hybrids based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Molecular marker analysis confirmed the predominance of A. incana alleles in A. × pubescens [15,21], indicating that hybrids tend to backcross to A. incana. In the studied populations in Serbia, A. incana was also identified as the mother species, because putative hybrids were found only in A. incana populations.…”
Section: Hybrids In Studied Populationsmentioning
confidence: 90%
See 3 more Smart Citations
“…Molecular marker analysis confirmed the predominance of A. incana alleles in A. × pubescens [15,21], indicating that hybrids tend to backcross to A. incana. In the studied populations in Serbia, A. incana was also identified as the mother species, because putative hybrids were found only in A. incana populations.…”
Section: Hybrids In Studied Populationsmentioning
confidence: 90%
“…Considering various leaf morphological traits, hybrids between black and grey alder overlap with one or both parents or hold an intermediate position and appear to be closer to A. incana [14,16,18]. Multivariate analysis of leaf morphological traits has shown that hybrids have an intermediate position and are closer to A. incana [14,15,19,20]. It was reported by [39] that the germination of a hybrid seed was only successful when A. incana For A. rohlenae, a weak positive correlation between NV and CS was determined in the population PK (R 2 = 0.113, p < 0.05).…”
Section: Hybrids In Studied Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Vyt ėnai progeny plantation, progenies from 5 out of 10 investigated GCUs were planted: JUO (OP families 135 and 139), MIK (OP family 97), PAZ (OP family 89), BAT (OP family 121), and VIL (OP family 103) (Figure 5). While sampling, care was taken to select only morphologically pure A. glutinosa trees, since in Lithuania, A. glutinosa and Alnus incana have an overlapping distribution [1,43] and the species are known to hybridize occasionally [44][45][46]. Identification of A. glutinosa samples followed the morphological description provided in Flora of Lithuanian TSR [47].…”
Section: Samplingmentioning
confidence: 99%